DESIGN AND DEVELOPMENT SMART-IMBULANCE FOR EFFICIENCY OF ROAD EMERGENCY PRIORITIES - Rosyid Ridlo, Al Hakim; Miftakhul Hafidz, Sidiq; Agung, Pangestu; Ariep, Jaenul; Yanuar Zulardiansyah, Arief; Hendra, Purnawan; Rofingi, Aji; Slamet, Riyadi (Bajang Institute, 2021)
Medical emergency conditions required patients to be mobilized by ambulance quickly, precisely, and accurately. To save the patient, the ambulance acted as a helper and hope for the patient to survive until the patients reach the hospital. The ambulance has to go through the fastest and closest way to reach the hospital. However, problems arise when road conditions do not support the creation of the fastest and closest ambulance. Due to congested road conditions, it will be possible to delay the ambulance from reaching the hospital or other unwanted events. The road and traffic conditions that can be controlled for the smooth running of the ambulance need special attention. Smart-iMbulance framework modeling allows an ambulance to move quickly and precisely to reach the nearest hospital. This paper provides a transportation model for vehicles, an application model as an embedded program in an ambulance, and a traffic management plan as a solution offered for ambulances on the road.